Accurate simulation of transcranial ultrasound propagation for ultrasonic neuromodulation and stimulation - Robertson, James L B; Cox, Ben T; Jaros, J; Treeby, Bradley E (The Journal of the Acoustical Society of America, 2017)
Non-invasive, focal neurostimulation with ultrasound is a potentially powerful neuroscientific tool that requires effective transcranial focusing of ultrasound to develop. Time-reversal (TR) focusing using numerical simulations of transcranial ultrasound propagation can correct for the effect of the skull, but relies on accurate simulations. Here, focusing requirements for ultrasonic neurostimulation are established through a review of previously employed ultrasonic parameters, and consideration of deep brain targets. The specific limitations of finite-difference time domain (FDTD) and k-space corrected pseudospectral time domain (PSTD) schemes are tested numerically to establish the spatial points per wavelength and temporal points per period needed to achieve the desired accuracy while minimizing the computational burden. These criteria are confirmed through convergence testing of a fully simulated TR protocol using a virtual skull. The k-space PSTD scheme performed as well as, or better than, the widely used FDTD scheme across all individual error tests and in the convergence of large scale models, recommending it for use in simulated TR. Staircasing was shown to be the most serious source of error. Convergence testing indicated that higher sampling is required to achieve fine control of the pressure amplitude at the target than is needed for accurate spatial targeting.
Keywords: časové faktory; Computer Simulation; numerická analýza pomocí počítače; Ultrasonic Therapy; pohyb těles; Pressure; tlak; Motion; Humans; počítačová simulace; Models, Theoretical; Time Factors; lidé; Ultrasonic Waves; teoretické modely; ultrazvuková terapie; ultrazvukové vlny; Numerical Analysis, Computer-Assisted